Systemic neutralization of TGF‐β attenuates osteoarthritis. Issue 1 (2nd February 2016) - Xie, Liang; Tintani, Francis; Wang, Xiao; Li, Fengfeng; Zhen, Gehua; Qiu, Tao; Wan, Mei; Crane, Janet; Chen, Qianming; Cao, Xu
Abstract : Osteoarthritis (OA) is a major source of pain and disability worldwide with no effective medical therapy due to poor understanding of its pathogenesis. Transforming growth factor β (TGF‐β) has been reported to play a role in subchondral bone pathology and articular cartilage degeneration during the progression of OA. In this study, we demonstrated that systemic use of a TGF‐β–neutralizing antibody (1D11) attenuates OA progression by targeting subchondral bone pathological features in rodent OA models. Systemic administration of 1D11 preserves the subchondral bone microarchitecture, preventing articular cartilage degeneration by inhibition of excessive TGF‐β activity, in both subchondral bone and the circulation. Moreover, the aberrant increases in the numbers of blood vessels, nestin + mesenchymal stromal/stem cells, and osterix + osteoblast progenitors were normalized by 1D11 systemic injection. Thus, systemic neutralization of excessive TGF‐β ligands effectively prevented OA progression in animal models, with promising clinical implications for OA treatment.